HERBAL PRODUCTS FOR PIG HEALTH - Kleijer-Ligtenberg, G.; Van Asseldonk, T.; Groot, M.; Halkes, B.; Binnendijk, G.; Johanna, J. Wagenaar (African Journal of Traditional, Complementary and Alternative Medicines, 2009)
On behalf of the Dutch interest group for biological farming (Biologica) a research project was initiated with the goal to increase the availability of herbal food additives of proven quality and efficacy [1]. This project involved poultry, dairy cows, and pigs, but the results of the latter animals are presented here, only. An inventory identified over 70 herbal preparations available for pig health. On basis of the available data, three products were selected for further clinical experiments. Two products contained (mainly) essential oil of oregano, the third was a mixture of approximately 10 plant (extract)s. For each product approximately 64 organic pigs were fed herbal additives from weaning until slaughter; growers in four pens; fatteners in three pens. Control groups of the same size and housing received feed without these herbs. Study-parameters were growth, feed conversion, mortality, requirement of additional veterinary treatment, meat percentage, back-fat, carcass- and organ-findings. Liver biopsies were evaluated for parameters relating to pig health. Herbal products showed positive effects on growth and/or feed conversion of weaners as a trend (p<0,12). No negative side effects were observed. Slaughter data were promising but not always consistent. To demonstrate health improvement, molecular parameters such as the amount of detoxifying enzymes (CYP450) can be measured. Tests with larger groups of animals are necessary to confirm the reported trends and to obtain significant treatment-effects. The Implementation of these herbal additives in farm management, their optimal dosage-levels, as well as the regulatory aspects of these herbal additives need further consideration. Acknowledgements: We thank the Dutch ministry of Agriculture, Nature and Food (LNV) for funding and all participating farmers and product suppliers for cooperating. [1] More details on www.fyto-v.nl